(3cJGH aj JaSjQ GdbQBfs
(3ChdgG (B:s
(3hai cdGe Gddg YR hLd GdPi dGjCJjg GdHGWd ef Hjf jOjg hdG ef Ndag , aOd eG bdfGg ef JUQja GdcdGe hPgGH GdeJcde dg ai GdLgGH GdeNJdaI Ydi Cfg EfeG jchf SHHkG ddJPcjQ Hg hGdOYGA Zdi Jageg s
(3BNQgG (B:s
(3BNQ GdehLhO efg GddBjJGf GdCNjQJGf ef ShQI GdeOKQ s
(3jJfGhd GdQO Ydi eNGdai GdeYJRdI ajeG ESJOdhG Hg ef BjGJ GdcJGH GdYRjRs
(3eQJH Ydi ShQ GdbQBfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs